The Effect of Giving Soursop Fruit Juice (Annona muricata, L.) on Hemoglobin Levels in Wistar Bunting Strain Rats Exposed to Cigarette Smoke - Prastanti, Ryan Hani; Nurdiana; Dewi, Mustika (Journal of Issues in Midwifery, 2024)
Background: Anemia in pregnancy can be caused by exposure to cigarette. A large number of free radicals can cause the number of erythrocytes to decrease. It takes a component to neutralize free radicals, namely antioxidants obtained from various fruits. Soursop contains sources of antioxidants such as flavonoid compounds, polyphenols, and vitamin C. Researchers want to know whether soursop juice can be used as an alternative antioxidant to prevent the decrease in hemoglobin levels of pregnant women. Objective: To determine the effect of giving soursop juice on hemoglobin levels of pregnant white rats with exposure to cigarette smoke. Methods: The experimental laboratory research was designed using the Randomized Post Test Only Control Group Design method. The experimental animal samples were 20 pregnant female Wistar (Rattus norvegicus) rats composed of two control and three treatment groups. Rats were given soursop fruit juice from the first day of rearing until the 18th day of gestation and exposed to cigarette smoke from the 6th day until the 18th. Then blood samples were taken from the mother's heart to measure the hemoglobin level. Results: The results of the hemoglobin level test showed that there was difference between the treatment group and control group. There is an increasing trend from the postitive control group to treatment group. Conclusion: Giving soursop fruit juice can prevent the decrease in hemoglobin levels of pregnant rats exposed to cigarette smoke. Keywords: anemia, free radicals, antioxidants, vitamin C.